The Role of Green Leadership and Green Organizational Culture on Corporate Sustainability Mediated by Employee Performance - Widjanarko, Wirawan; Hadita, Hadita; Jumawan, Jumawan; Hasanuddin, Hasanuddin (Dinasti Publisher, 2025)
The purpose of this literature research is expected to help hypotheses for future authors in determining research related to human resource management. The research article on the role of green leadership and green organizational culture on company sustainability mediated by employee performance is a scientific literature article within the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct literature reviews of relevant previous articles. The data used in this study are secondary data, sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green Leadership affects employee performance; 2) Green Organizational Culture affects Employee Performance; 3) Green Leadership affects Company Sustainability; 4) Green Organizational Culture has an effect on Employee Performance; 5) Employee Performance has an effect on Corporate Sustainability; 6) Green Leadership has an effect on Corporate Sustainability mediated by Employee Performance; and 7) Green Organizational Culture affects Company Sustainability mediated by Employee Performance.